Penerapan Discovery Learning pada Keterampilan Menulis Teks Prosedur di Kelas VII SMP Negeri 2 Kota Pematangsiantar Tahun Ajaran 2023/2024 - Manalu, Monika Krisdianti; Harahap, Eddy Pahar; Ningsing, Arum Gati (Jurnal Ilmiah Dikdaya, 2024)
Discovery learning is a learning activity that requires students to discover concepts through a series of data or information. In accordance with the 2013 curriculum, learning is no longer student-centered but is more interactive. One aspect of language is writing, where students are required to produce written work, including writing procedural texts. The discovery learning model will be applied by Indonesian language teachers with KD 3.5 procedural texts. This research uses a qualitative approach with a descriptive type. Qualitative research methods are often called naturalistic research methods because the research is carried out in natural conditions (natural settings). In other words, this research uses real evidence that can actually be found in the field. Judging from the learning process, student activities will take on a new color, not only that, the learning class that has been implemented by this teacher uses a learning model that is in accordance with the 2013 curriculum. This discovery learning model has been successfully implemented by teachers in class VII 11, this has been proven in class VII 11, that identifying procedural texts is in accordance with the discovery learning learning model. The planning aspect, has met scientific requirements, according to the teacher's RPP and the syntax of the implementation aspect, using the discovery learning model in procedure text material in class VII 11 of SMP Negeri 2 Pematangsiantar City, students are given the opportunity to think, discover, argue and collaborate with each other through learning activities guided by the teacher. The evaluation aspect uses two processes, namely observing student activity and assignments or practice